From Fitnah to Thaura: The Metamorphosis of the Arab-Muslim Protest Movements - Alisa Shishkina; Leonid Issaev (Religions, 2017)
Since 2011, the Arab world has entered a period of political turbulence accompanied by widespread growth of protest activity. The events that were metaphorically called the “Arab Spring” referring to the “Spring of Nations” of 1848, affected virtually all countries of the Middle East and North Africa. In Libya, Syria, and Yemen, antigovernment demonstrations led to almost complete destruction of statehood raising the question of the existence of these political entities in their former borders. Egypt and Tunisia ended up with a change in the ruling regimes that repeated many times. The ruling elites of other Arab countries, having experienced the wrath of the Arab streets to varying degrees, managed to stay in power. The “Arab Spring” events should be more adequately viewed in the framework of “fitnah”, a form of protest traditional in the Arab-Muslim political culture. Indeed, since the emergence of Islam, fitnah was one of the most common forms of protest activity in the Middle East. However, in the last two centuries, it was replaced by “thaura” or the “revolution,” much more common in the European mentality. While the term "fitnah" has mainly negative connotations, “thaura” has been praised in every possible way and even became the basis for commemorative practices. This paper makes an attempt to compare these two forms of protest in the Muslim world.